Randomised trial on effect of involving media reporters in salt reduction programme to increase media reports and the public's knowledge, belief and behaviors on salt and health: Changzhi reporters trial. - Zhifang Li (Public Library of Science (PLoS), 2021)
Objective To assess the effects of a novel mass media intervention in increasing media reports on salt and health by involving media reporters in a scientifically well designed salt reduction trial. Methods We recruited and trained 66 media reporters in Changzhi, Shanxi province, China to conduct a randomized controlled trial on blood pressure lowering effect of salt substitute in Dec, 2012 and Jan 2013 among their own relatives or friends (253 from 129 families in the salt substitute arm and 263 from 133 families in the control arm for two months). We shared trial results and other information on salt and health with the reporters within a month after the trial. We monitored all local newspapers for the number of relevant articles in 3 months before, 3 months during and 3 months after the intervention and at the 6th, 12th, 18th, 24th and 48th months after the intervention. Additionally, we conducted two independent surveys on knowledge, belief and behaviours of salt and health among local citizens before and after the intervention. Results As expected, systolic blood pressure was reduced significantly more in the salt substitute than the control group (-4.7±11.0 mmHg vs -2.6±10.3 mmHg, p<0.001) in the randomized trial. The monthly mean number of relevant articles increased from 0.7 before to 1.7 during (p = 0.263), and further to 6.0 after the intervention (p<0.001), and varied from 2 (p = 0.170) to 4 (p = 0.008) from the 6th to 48th month; the awareness of knowledge on salt and health among local citizens improved significantly after the intervention. Conclusions Media reporters' participation in a well-designed salt reduction trial significantly increased the number of relevant media reports, and the effect was sustained for a prolonged period. Future mass media public health education programs should consider this innovative strategy for better and sustained impacts.